BIMBINGAN TEKNIS PEMASANGAN PIPA POLYETHYLENE UNTUK SISTEM AIR BERSIH BANJAR KAJA-KAUH DESA SUDAJI - I N. Suweden; A.A.A. Suryawan; I W. Dana; I G.N.K. Arsana (Buletin Udayana Mengabdi, 2016)
Kaja-Kauh sub-village of Sudaji village is a nestled community in the hills, with a population of 231households (1,155 people), until now could not enjoy clean water because there are constraints on the pipingsystem. In order to meet the needs of everyday people have to carry water from source water from othervillages higher elevation, such as Sekumpul and Lemukih villages using a piping system. In this activity, thepipe material provided by the Rotary Club Bali-Taman in collaboration with the Korean Rotary Club. Whilethe physical execution of the installation of the pipeline in the field of mutual assistance is done by localpeople. Given the pipe material given is kind of a new pipe is a pipe High Density Poly Ethylene (HDPE)that is not yet known by the public, especially in the process of these connections by using a system ofcompression joint, the team of Udayana University needs to provide technical assistance in the form ofguidance and supervision of the implementation of pipe laying. After receiving technical assistance from theimplementation team devotion Udayana University, the community has been able to install and connectHDPE pipe properly. Water has been flowing smoothly, both from the water spring to the reservoir and fromthe reservoir to residents housing. But not all houses connected to water systems because of the constraints ofsociety's ability to provide pipes and water meter that must be provided by each water user.